Hyper-Fractionated Radiotherapy for Soft Tissue Sarcoma: Results of the Second Study of Hyper-Fractionated Radiotherapy. (1999) - Jacob, R.; Gilligan, D.; Robinson, M.; Harmer, C.
Abstract : Purpose and Method. Hyper-fractionated radiotherapy for treatment of soft tissue sarcomas is designed to deliver a higher total dose of radiation without an increase in late normal tissue damage. In a previous study at the Royal Marsden Hospital, a total dose of 75 Gy using twice daily 1.25 Gy fractions resulted in a higher incidence of late damage than conventional radiotherapy using 2 Gy daily fractions treating to a total of 60 Gy. The current trial therefore used a lower dose per fraction of 1.2 Gy and lower total dose of 72 Gy, with 60 fractions given over a period of 6 weeks. Subjects. A total of 37 patients (22 males and 15 females) with a median age of 56 years (range 19–88 years) were treated. Results. Of eight patients treated pre-operatively, six showed a partial response and in two the tumour was static. The maximum acute toxicities were grade 1 in eight, grade 2 in 14 and grade 3 in 15 patients. Late toxicities of the skin were graded 1 in 10 and grade 2 in nine patients. Five patients complained of pain in the irradiated bone and soft tissues, which was of moderate severity (grade 2). Stiffness was graded 2 in three patients and severe (grade 3) in one.Three patients had moderate and one patient had severe lymphoedema following treatment. The 5-year recurrence-free survival probability of patients treated radically was 76%. Following excision of local recurrences the study group had a disease-free survival probability of 86% at 5 years. Discussion. The regime is well tolerated with comparable local control and late complication rates to standard daily fractionated therapy.The potential benefit of this regime needs to be defined in a prospective randomized trial.